Ginseng for managing menopausal woman's health: A systematic review of double-blind, randomized, placebo-controlled trials. Issue 38 (September 2016) - Lee, Hye Won; Choi, Jiae; Lee, YoungJoo; Kil, Ki-Jung; Lee, Myeong Soo
Abstract: Background: The aim of this systematic review was to update, complete, and critically evaluate the evidence from placebo-controlled randomized clinical trials (RCTs) of ginseng for managing menopausal women's health. Methods: We searched the literature using 13 databases (MEDLINE, AMED, EMBASE, the Cochrane Library, 6 Korean Medical, and 3 Chinese Databases) from their inception to July 2016 and included all double-blind RCTs that compared any type of ginseng with a placebo control in postmenopausal women. The methodological quality of all studies was assessed using a Cochrane risk of bias tool. Results: Ten RCTs met our inclusion criteria. Most RCTs had unclear risk of bias. One RCT did not show a significant difference in hot flash frequency between Korean red ginseng (KRG) and placebo. The second RCT reported positive effects of KRG on menopausal symptoms. The third RCT found beneficial effects of ginseng (Ginsena) on depression, well-being, and general health. Four RCTs failed to show significant differences in various hormones between KRG and placebo controls except dehydroepiandrosterone. Two other RCTs failed to show effects of KRG on endometrial thickness in menopausal women. The other RCT also failed to show the effects of American ginseng on oxidative stress markers and other antioxidant enzymes. Conclusion: Our systematic review provided positive evidence of ginseng for sexual function and KRG for sexual arousal and total hot flashes score in menopausal women. However, the results of KRG or ginseng failed to show specific effects on hot flash frequency, hormones, biomarkers, or endometrial thickness. The level of evidence for these findings was low because of unclear risk of bias.